Risk Factors for Severe Residual Headache in Cerebral Venous Thrombosis. Issue 2 (February 2021) - Ji, Kangxiang; Zhou, Chen; Wu, Longfei; Li, Weili; Jia, Milan; Chu, Min; Wu, Di; Hou, Chengbei; Duan, Jiangang; Meng, Ran; Ji, Xunming
Abstract : Background and purpose: Which factors will influence the presence of severe residual headache after cerebral venous thrombosis (CVT) is unclear. The purpose of this study was to identify risk factors for severe residual headache in a large single-center cohort of patients with CVT. Methods: We consecutively included eligible patients with CVT from a prospective stroke registry. Severe residual headache was defined as a residual headache attack requiring bed rest or hospital admission within 1 month before the last follow-up visit. We identified the risk factors of severe residual headache in all survivors and in those with favorable functional outcome (a modified Rankin Scale score, 0–2). Results: A total of 325 patients' data were analyzed. At the last follow-up (median 13 months), 43 patients (13.2%) reported severe headache. In the multivariable analysis, isolated intracranial hypertension (odds ratio [OR], 3.309 [95% CI, 1.434–7.634]; P =0.005), CVT recurrence (OR, 4.722 [95% CI, 1.639–13.602]; P =0.004), and no recanalization (OR, 10.158 [95% CI, 4.194–24.600]; P <0.001) were independently associated with severe headache. Severe headache was more frequent in patients with unfavorable outcome (11/25 [44.0%] versus 32/300 [10.7%]; P <0.001). In patients with favorable outcome, the risk factors for severe headache were isolated intracranial hypertension (OR, 3.236 [95% CI, 1.268–8.256]; P =0.014) and no recanalization (OR, 7.863 [95% CI, 3.120–19.812]; P <0.001). Conclusions: Isolated intracranial hypertension, CVT recurrence, and no recanalization increased the risk for severe residual headache after CVT. Abstract : Supplemental Digital Content is available in the text.